Proposta Metodológica para o Ensino do Voleibol Escolar: possibilidades de intervenção na prática pedagógica - Magalhaes, Ueder Moreira (2020)
Over the seventeen years of experience in school teaching I realized that sports content is predominant in physical education classes, however, volleyball is discredited by prejudice and learning difficulties. This study aimed to describe and analyze a te